Thermoelectric transport in conducting polymers - Abdul Rauf Mohamed Raffi (Nanyang Technological University, 2021)
With the rising need to search for alternative energy technologies, the research on thermoelectric materials (TE) has been increasing in importance. Typical thermoelectric materials are inorganic materials, but recent research shows the potential and benefits of using organic materials. The seebeck coefficient and electrical conductivity of organic materials must be optimized before they can be used in thermoelectric applications. In this project, different dopants with varying concentration are used to study the thermoelectric properties of P3HT and PBTTT. Sequential doping is used to control the doping level of the polymers. The effectiveness of the doping is highlighted by doing a UV-vis test. The seebeck coefficient and electrical conductivity were measured using a new lithography-free resistance thermometry-based technique.